The Effects of an Electronic Daily Behavior Report Card on Student's Challenging Behavior. Issue 3 (September 2021) - Riden, Benjamin S.; Taylor, Jonté C.; Scheeler, Mary Catherine; Lee, David L.; McCloskey, Andrea V.
An ABAB reversal design was utilized to examine the effects of an electronic daily behavior report card (eDBRC) on non-compliant, off-task, and disruptive classroom behaviors of a 16-year-old with autism spectrum disorder and a 17-year-old with an intellectual disability. The intervention was implemented by two preservice teachers (interventionists) in their final student teaching requirement. In addition to visual analysis procedures, effect sizes (i.e., Tau-U) were calculated. The research questions were: (1) What are the effects of eDBRCs on participants' disruptive and challenging classroom behaviors, (2) To what extent do preservice teachers implement eDBRCs with fidelity, and (3) Are eDBRCs a socially valid intervention? Upon completion of our study the eDBRC was effective in reducing non-compliant, off-task, and disruptive behaviors. We found that preservice special educators can implement a complex behavior intervention to support the outcomes of their learners during the student teaching experience. Additionally, we suggest eDBRCs are an acceptable intervention for students with autism spectrum disorder and intellectual disabilities.